Proses Perubahan Sosial Pengembangan Wisata Pesisir Payangan di Desa Sumberejo Kecamatan Ambulu Kabupaten Jember - Indah Tri Qurniawati; Diah Puspaningrum (Fakultas Pertanian Universitas Jember, 2020)
One of the touris destinations which recenltly developed massively is the Payangan Beach. This tourism destination develops quite rapidly, this condition allows a social change among the society. The location of the research using purposive method. This research using case study method. The informants are chosen by using purposive sampling. The data collection is conducted by using interview, non-participatory observation, and documentation study. The data analysis is conducted by using Miles and Huberman’s method. The result of this research reveals: (1) there are internal factors includes the finding of a new destination and external factor is the environmental change to cause the social changes to happen. (2) the pushing factors of the social change are open stratification of the society, people respect, and the future orientation. (3) The inhibition factor to alter the social change to happen is the limited capability of human resources. (4) the process of the social change which starts from the change channels. The next stage of the process of social change is the adjustment conducted by the institutions and society. The last stage of the process of social change is seen on the occurrence of disorganization and reorganization Keywords : beach, social change, tourism destination